Persepsi Guru Pendamping Khusus di SD Inklusi Pada Masa Pandemi Covid-19 - Rara Ajeng Pratiwi; Eka Pudji Astuti; Setia Budi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2022)
With the current state of the COVID-19 pandemic, the learning process must continue with the implementation of an online learning system. This study aims to determine the views of special educator teachers who handle children with special needs during the online learning process. The purpose of this research is that it can be used as a reference or reading source for Special Assistance Teachers (GPK) and other educator activists in making policies when implementing online learning for children with special needs who attend inclusive schools. This research can be categorized as one of the interesting researches that is using descriptive method with a qualitative approach. Where this research was conducted by observing and understanding the problems that arise in the object of research using specific data collection techniques from respondents (GPK who accompanies ABK in inclusive schools during online learning during the pandemic) through questionnaires. The results of this study indicate that there are still learning effectiveness problems that arise due to the integration of conventional learning into online learning. Based on these problems, ABK, parents and also teachers who teach must continue to receive assistance and motivation so that they can adapt to learning that uses digital media.